2013
DOI: 10.1007/s00586-013-2921-3
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional analysis of brace biomechanical efficacy for patients with AIS

Abstract: Purpose Corrective three dimensional (3D) effect of different braces is debatable. We evaluated differences in in-brace radiographic correction comparing a custom thoracic-lumbo-sacral-orthosis (TLSO) (T) brace to a Chêneau type TLSO (C) brace using 3D EOS reconstruction technology. Our primary research question was the 3D effect of brace on the spine and in particularly the apical vertebra rotation (AVR). Methods This was a retrospective comparative analysis of patients with adolescent idiopathic scoliosis wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…This is slightly better than the 50% cohort improvement previously reported by Courvoisier et al [5]. The absolute Cobb angle correction observed in this study was similar to the one previously reported by Lebel et al [19] (-10.4° against ~14°), but VAR correction was lower (-1.7° against -6.5°). Comparison with previous studies, in particular concerning absolute values of correction, is difficult because of differences in the initial cohort (age, curve topology), brace compliance [3], etc.…”
Section: Discussionsupporting
confidence: 85%
“…This is slightly better than the 50% cohort improvement previously reported by Courvoisier et al [5]. The absolute Cobb angle correction observed in this study was similar to the one previously reported by Lebel et al [19] (-10.4° against ~14°), but VAR correction was lower (-1.7° against -6.5°). Comparison with previous studies, in particular concerning absolute values of correction, is difficult because of differences in the initial cohort (age, curve topology), brace compliance [3], etc.…”
Section: Discussionsupporting
confidence: 85%
“…11 The purpose of this study was to analyze the variability of the long-term effects of bracing on AIS. The main finding of the study is that the Chêneau brace induces a significant decrease in kyphosis, lordosis, and PT.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found no statistically significant immediate modification of transverse plane parameters. 4 Lebel et al 11 compared the differences in immediate 3D effects between the Chêneau brace and the Boston brace by assessing 3D reconstructions. They demonstrated that the Chêneau brace had a significant de-rotation effect compared with the Boston brace.…”
Section: Discussionmentioning
confidence: 99%
“…Label et al evaluated the in in-brace radiographic correction for patients treated with either the thoraco-lumbo-sacral orthosis (TLSO) or the RCOs. Following bracing, they found that the apical vertebral rotation was significantly reduced by the RCOs when compared with the TLSO by on average 8.2°v s. 4.9° [54]. Another study evaluated the therapeutic success of the RCOs.…”
Section: Non-surgical Managementmentioning
confidence: 99%